Spaceborne Synthetic Aperture Radar Survey of Subsidence in Hampton Roads, Virginia (USA). Issue 1 (December 2017) - Bekaert, D.; Hamlington, B.; Buzzanga, B.; Jones, C.
Abstract Over the past century, the Hampton Roads area of the Chesapeake Bay region has experienced one of the highest rates of relative sea level rise on the Atlantic coast of the United States. This rate of relative sea level rise results from a combination of land subsidence, which has long been known to be present in the region, and rising seas associated with global warming on long timescales and exacerbated by shifts in ocean dynamics on shorter timescales. An understanding of the current-day magnitude of each component is needed to create accurate projections of future relative sea level rise upon which to base planning efforts. The objective of this study is to estimate the land component of relative sea level rise using interferometric synthetic aperture radar (InSAR) analysis applied to ALOS-1 synthetic aperture radar data acquired during 2007–2011 to generate high-spatial resolution (20–30 m) estimates of vertical land motion. Although these results are limited by the uncertainty associated with the small set of available historical SAR data, they highlight both localized rates of high subsidence and a significant spatial variability in subsidence, emphasizing the need for further measurement, which could be done with Sentinel-1 and NASA's upcoming NISAR mission.